2009
DOI: 10.1007/s00198-009-1103-y
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density is not associated with angiographically determined coronary atherosclerosis in men

Abstract: The prevalence of low BMD is very high in men undergoing coronary angiography. However, low BMD is not associated with angiographically determined coronary atherosclerosis in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Similar results have been reported in China [12, 13, 15] and Korea [31]. In addition, Beer et al [33] reported that low hip BMD was not associated with angiographically determined coronary atherosclerosis in men, consistent with our results. This indicates that bone loss does not affect the structural changes that occur in atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been reported in China [12, 13, 15] and Korea [31]. In addition, Beer et al [33] reported that low hip BMD was not associated with angiographically determined coronary atherosclerosis in men, consistent with our results. This indicates that bone loss does not affect the structural changes that occur in atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…In 340 women, severe mitral annular calcification was associated with higher prevalence of osteoporosis diagnosed by DXA (40). By contrast, several studies show that, after adjustment for age and other confounders, the association between BMD and coronary artery calcification is not significant (27,35,41,42).…”
Section: Vascular Calcification and Fracture Riskmentioning
confidence: 92%
“…OP affects 44 million Americans (55%) over the age of 50 years [ 1 , 2 ]. According to data from the World Health Organization (WHO), elderly individuals will comprise 20% of the population by 2050 [ 3 5 ], increasing the prevalence of OP and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%